Liquid Chromatographic Determination of Neurotransmitter Serotonin from Human Cerebrospinal Fluid Using 2-Hydroxynaphtaldehyde as Derivatizing Reagent - Panjwani, Indra; Arain, G.M.; Khuhawar, M.Y. (Asian Journal of Chemistry, 2013)
The reagent 2-hydroxy naphthaldehyde was used for the spectrophotometric and reversed phase HPLC separation and determination of glycine, lysine, octopamine, serotonin and tyramine. The derivatives formed were examined spectrophotomatrically for the effects of pH, derivatizing reagent concentration and heating time in aqueous-methanolic solution. The derivatives indicated molar absorpitivity of 2.8 × 103-7.7 × 103 L mol-1 cm-1. The spectrophotometric calibration curves were observed within 1.0-20.0 μg mL-1 at lmax 420 nm. The derivatives of 2-hydroxy naphthaldehyde were easily eluted and separated from Kromasil 100 C-18 10 μm (25 cm × 0.46 cm id) column. The elution was carried out with methanol: water: acetonitrile and acetate buffer (0.1 M) (pH 6) (47:25:18:10 v/v/v/v) with a flow rate of 1 mL min-1 and UV detection was at 240 nm. A number of amino acids and pharmaceutical additives were checked and did not interfere to the determination. The method was successfully applied for the determination of lysine from pharmaceutical preparation and serotonin and glycine from human cerebrospinal fluid. The analysis was further supported by standard addition method. The recovery of lysine from pharmaceutical preparation was 97.46 % with RSD 2.8 %. Glycine and serotonin were determined from human cerebrospinal fluid and found 8.13-16.118 μmol L-1 and 3.92-7.44 nmol L-1 with RSD 1.6-3.3 and 1.4-3.6 %.